Doing augmented reality: a discourse analysis - Bergamin, Mateus Mathias dos Santos (2021)
Since its emergence in the 90s, augmented reality has been referred to as the superimposition of virtual objects on the view of the physical world, and holds a promise to fundamentally change the way we interact with the digital universe. However, AR was never able to achieve such objectives, and after the Google Glass Experiment in 2013, what is evident is a conflict between the research visions and consumer expectations. Seeing that reality is done through discursive practices and enactments, this thesis examines how AR is done by those who are involved in its development, its promotion and its use, through textual and discourse analysis, aiming to understand the vision behind its development. We first analyse the emergence and development of AR, following with the analysis of the Google Glass Experiment, as a materialization of the technology. Taking into consideration the potential for behavior and lifestyle change held in AR development, understanding the underlying discourses and visions is of crucial importance as we bring technology to our reality. As a result we have a better assessment of the current technology situation as well as insights for future development and solutions in the field of augmented reality.